Case report: Heart Mate III for systemic right ventricular support in a patient with hypoplastic left heart syndrome - Hanuna, Maja; Pabst von Ohain, Jelena; Haas, Nikolaus; Mueller, Christoph S.; Dalla-Pozza, Robert; Fischer, Marcus; Born, Frank; Kamla, Christine; Jakob, Andre; Hagl, Christian; Hörer, Jürgen; Michel, Sebastian G. (Frontiers in Cardiovascular Medicine, 2023)
Ventricular assist device implantation presents a possible bridge to heart transplantation for patients with failing Fontan physiology. However, evidence regarding outcome and possible pitfalls associated with the Fontan circulation is still insufficient. We describe the course of a 13-year-old male, who was born with hypoplastic left heart syndrome and underwent HeartMate III implantation due to refractory failure of the systemic right ventricle.